Program Senam Rutin Dalam Upaya Meningkatkan Kesehatan Masyarakat di Dusun Godean Desa Kucur - Asri, Yuni; Priasmoro, Dian Pitaloka (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: Routine exercise programmes are a strategic effort to improve the physical and mental health of the population. The activities are designed to involve different age groups and fitness levels through structured and varied exercise movements. Objective: The purpose of this community service is to improve public health in Godean of Kucur Village, through a routine exercise programme Method: This exercise is carried out in the courtyard of the citizen's house or on the side of the street in RW 10 Godean of Kucur Village and is held every Saturday at 3 P.M Result: The results of the routine exercise showed that there were 46 people who attended the gym in RW 10 Godean of Kucur Village, Dau district, and Malang district. Following this routine exercise, the physical and mental well-being of the participants underwent significant changes. Citizens felt more fresh, relaxed, and happy to socialize with other citizens Conclusion: To ensure the sustainability and effectiveness of the programme, a number of follow-up measures have been planned, including more intensive promotion and socialization, as well as collaboration with health institutions to provide health information support